2000
DOI: 10.2135/cropsci2000.402358x
|View full text |Cite
|
Sign up to set email alerts
|

Variation among Maize Inbred Lines and Detection of Quantitative Trait Loci for Growth at Low Phosphorus and Responsiveness to Arbuscular Mycorrhizal Fungi

Abstract: Maize (Zea mays L.) growth at low soil P levels is affected both by inherent physiological factors as well as interactions with soil microbes. The objectives of this study were (i) to quantify differences among maize inbred lines for growth at low P and response to mycorrhizal fungi, and (ii) to identify quantitative trait loci (QTL) controlling these traits in a B73 × Mo17 recombinant inbred population. Shoot dry weight and root volume were measured in the greenhouse after 6 wk of growth in a factorial experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
203
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(230 citation statements)
references
References 15 publications
25
203
2
Order By: Relevance
“…Seeds of maize (Zea mays) RILs from the Intermated B73 and Mo17 (IBM) population were obtained from Dr. Shawn Kaeppler (University of Wisconsin, Madison;Senior et al, 1996;Kaeppler et al, 2000). Previous screening indicated that RILs 337, 133, and 177 had low RCA and RILs 196,199, and 345 had high RCA under low-N conditions.…”
Section: Plant Materialsmentioning
confidence: 99%
“…Seeds of maize (Zea mays) RILs from the Intermated B73 and Mo17 (IBM) population were obtained from Dr. Shawn Kaeppler (University of Wisconsin, Madison;Senior et al, 1996;Kaeppler et al, 2000). Previous screening indicated that RILs 337, 133, and 177 had low RCA and RILs 196,199, and 345 had high RCA under low-N conditions.…”
Section: Plant Materialsmentioning
confidence: 99%
“…Root colonization varied more widely in the C 3 than in the C 4 grasses, corresponding with stronger reductions in allocation to AMF at high phosphorus in C 3 than C 4 grasses. Root colonization is at best a weak predictor of carbon and nutrient exchange (Noyd et al 1995, Wilson and Hartnett 1998, Kaeppler et al 2000, Jifon et al 2002, so it is surprising that this response was associated with effective reductions in allocation to non-mutualistic AMF.…”
Section: Differences Between the Functional Groupsmentioning
confidence: 99%
“…Both inbred lines (Mo17, B73) and the B73 3 Mo17 hybrid have been extensively studied. As a result, QTL studies for several traits performed on the progeny of this cross have been published (Stuber et al 1992;Kaeppler et al 2000;Mickelson et al 2002;Carson et al 2004). Seed for the eight selected SILs and their crosses to inbred line Mo17 was increased in the winter of 2003 in Puerto Rico.…”
Section: Methodsmentioning
confidence: 99%